Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.resuscitation.2014.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Medical Priority Dispatch (MPD) and Criteria Based Dispatch (CBD) relating to cardiac arrest calls

Abstract: Pre-arrival CPR instructions were offered faster and more frequently in the CBD system, but in both systems chest compressions were delayed 3-4min. Earlier recognition of cardiac arrest and improved CPR instructions may facilitate earlier lay rescuer CPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 63 publications
(73 reference statements)
2
47
0
2
Order By: Relevance
“…11 The median time to recognize OHCA was 60 s, and the median time to start DA-CPR was 220 s. Our results are within the range of previously published results. In dispatch centers using the Medical Priority Dispatch (MPD) system, the proportion of recognized OHCA was between 79 and 92%, with a median time from the call to the OHCA recognition ranging from 69 to 219 s, and the median time from the call to the initiation of DA-CPR from 176 to 285 s. 7,8,[12][13][14] In a recent study with MPD, 28 of the 176 s of delay in provision of the first DA-CPR were attributed to the dispatchers asking needless questions, suggesting a potential for better training of dispatchers to shorten their interviews when using this system. 8 In one dispatch center using a CBD system, OHCA was recognized in 77% of the cases, with a median time from the call to the OHCA recognition of 102 s and a median time from the call to the initiation of DA-CPR at 222 s. 12 Compared to other settings, the EMS travel time to the patient was longer, probably due to the mountainous geography of our state.…”
Section: Resultsmentioning
confidence: 99%
“…11 The median time to recognize OHCA was 60 s, and the median time to start DA-CPR was 220 s. Our results are within the range of previously published results. In dispatch centers using the Medical Priority Dispatch (MPD) system, the proportion of recognized OHCA was between 79 and 92%, with a median time from the call to the OHCA recognition ranging from 69 to 219 s, and the median time from the call to the initiation of DA-CPR from 176 to 285 s. 7,8,[12][13][14] In a recent study with MPD, 28 of the 176 s of delay in provision of the first DA-CPR were attributed to the dispatchers asking needless questions, suggesting a potential for better training of dispatchers to shorten their interviews when using this system. 8 In one dispatch center using a CBD system, OHCA was recognized in 77% of the cases, with a median time from the call to the OHCA recognition of 102 s and a median time from the call to the initiation of DA-CPR at 222 s. 12 Compared to other settings, the EMS travel time to the patient was longer, probably due to the mountainous geography of our state.…”
Section: Resultsmentioning
confidence: 99%
“…Diversos estudos demonstram a eficiência do MPDS na detecção de PCR (21)(22)(23)(24)(25) . O protocolo utilizado garante que, diante de uma demanda volumosa, seja possível detectar e responder rapidamente a esse tipo de solicitação.…”
Section: Discussionunclassified
“…Moreover first-aid guidance by telephone is time consuming, and a wholly scripted approach where all first aid measures were instructed is not likely to be effective. Indeed, comparison between a system strictly scripted EMCC guidance and a system where more decisions are left to the dispatchers’ discretion showed that CPR-instructions where offered faster and more frequently in the latter [6]. …”
Section: Discussionmentioning
confidence: 99%
“…Norwegian EMCC operators use a criteria-based dispatch (CBD) system (Index) suggesting appropriate first-aid measures based on caller descriptions of signs and symptoms at the operator’s discretion [6]. We compared the performance of this use of the dispatch system to performance if the Index had been used as a strict algorithm.…”
Section: Methodsmentioning
confidence: 99%